Formation and Wet Removal of Organic and Titanium-Containing Residues on Patterned TiN/Porous Low-k Structure. (19th October 2018) - Le, Q. T.; Kesters, E.; Holsteyns, F.
Abstract : The formation of the residues after patterning of a patterned metal hard mask/dielectric stack was characterized using surface-sensitive methods (attenuated total reflection-Fourier transform infrared spectroscopy and angle-resolved X-ray photoelectron spectroscopy) and scanning electron microscopy. The effect of a reducing plasma post-etch treatment (PET), aging, and moisture on the evolution of the residues was investigated. Both polymer-based (CFx) and metal-containing (TiFx) residues were identified on the exposed surface of the stack. Without the PET, the XPS data collected at different take-off angles suggested that the metal-containing residues were covered by a thin layer of polymer-based residues. The metal-containing residues were found to continue to evolve as a function of aging time if the layer of polymer-based residues was removed by the PET, making the metal hard mask in direct contact with cleanroom air. Exposing the MHM/dielectric stack to a 100% humidity environment did not induce further growing of the TiFx residues. Despite the PET only had limited removal of the TiFx-based residues, it was efficient in removing the polymer-based CFx residues, which in turn led to a better cleaning efficiency after the subsequent wet clean. The results in this study also confirmed that diluted HF dissolved TiFx-type residues and had no CFx removal capability. Although only two chemicals are shown as examples for post-etch residue removal, the type of test structure and methodology shown in this study can be applied for investigation and optimization of any other chemical mixture candidates for cleaning purpose.